THE ROLE OF OUR NATIONAL VALUES IN SHAPING THE SPIRITUALITY OF YOUNG PEOPLE (Prima Journal of Integrated Studies, 2026)
This article examines the role of national values in shaping the spirituality of young people. National values are analyzed as a system of moral, cultural, social and educational principles that influence the worldview, behavior, identity and civic responsibility of the younger generation. The article emphasizes that respect for parents and elders, family solidarity, hospitality, diligence, patriotism, tolerance, honesty, modesty and responsibility are not only traditional moral categories, but also important pedagogical resources in modern education.
Keywords: National values, spirituality, young people, moral education, identity, family, patriotism, education, cultural heritage.